Comparative Review of Endoscopic Devices Articulations Technologies Developed for Minimally Invasive Medical Procedures - Julien Catherine; Christine Rotinat-Libersa; Alain Micaelli (Applied Bionics and Biomechanics)
This study introduces a comparative performance analysis of the technological solutions that have been used to build distal active articulations for minimally invasive medical procedures. The aim is to provide a practical and concise database and classification tool for anyone that wants to learn more about the technologies involved in minimally invasive medical devices, or for any designer interested in further improving these devices. A review of the different articulations developed in this field is therefore performed and organized by both actuation technology and structural architecture. Details are presented concerning the mechanical structures as well as the actuation and the mechanical transmission technologies available. The solutions are evaluated keeping as a reference some chosen required performances and characteristics for minimally invasive surgical procedures. Finally, a quantified comparison chart of these devices is given regarding selected criteria of interest for minimally invasive surgical application.